2 - Vivência em ‘‘Epistemologias Negras’’: desafios e perspectivas no ensino de Ciências Sociais na Universidade Federal de Pernambuco (UFPE) - Luís Soares; Rayza Silva; Ana Cláudia Rodrigues da Silva (Africa Development, 2025)
This article analyses the pedagogical experiences in the “Black Epistemologies” course at the Department of Anthropology and Museology at the Federal University of Pernambuco (UFPE). The main objective is to present Afro- referenced narratives from faculty members about the challenges of teaching black authors and authors who have historically been made invisible in the Social Sciences. These narratives are associated with the concepts of the Racial Device, Racism, Sexism and the White Self Ideal. The main techniques of this qualitative research were participants observation and writing. It is concluded that the “Black Epistemologies” course played a central role in the development of critical thinking among students and educators.